On some numerical iterative methods for Fredholm integral equations with deviating arguments: Dedicated to Professor Gheorghe Coman on the occasion of his 80th anniversary - MICULA, Sanda (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
In this paper we develop iterative methods for nonlinear Fredholm integral equations of the second kind with deviating arguments, by applying Mann's iterative algorithm. This proves the existence and the uniqueness of the solution and gives a better error estimate than the classical Banach Fixed Point Theorem. The iterates are then approximated using a suitable quadrature formula. The paper concludes with numerical examples. Mathematics Subject Classification (2010): 45B05, 47H10, 47N20, 65R20.